(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The authors reviewed a study in which the researchers used the example of the 2000 presidential election in the United States to demonstrate that political disputes with technology foundations do not resolve themselves via technological methods. On the other hand, I investigate the assumption that scientific investigation is inevitably politicized in environmental debates using examples like changing climate, genetic modification, and nuclear waste disposal. I’m going to look at three possible reasons for this. Second, science provides essential valid knowledge about existence to the contending parties of their own bodies, which are chosen in part because they assist in making sense of human wants and moral systems, as well as being rationalized as a result of this information. For a second, opposing disciplinary methods may be causally linked to rival political or ethical views that are founded on differing values, in order to explain the scientific origins of an environmental dispute.